1993
DOI: 10.1038/bjc.1993.456
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD59, a complement regulator protein and a second ligand of the CD2 molecule, and CD46 in normal and neoplastic colorectal epithelium

Abstract: SummaryCD59 (protectin) and CD46 (membrane cofactor protein, MCP) are membrane-bound complement regulator proteins which inhibit complement-mediated cytolysis of autologous cells. CD59, a phosphatidyl-inositol-anchored glycoprotein, inhibits the formation of the terminal membrane attack complex (MAC) of complement and was found to be a second ligand for CD2 contributing to T-cell activation. In 20 colorectal normal mucosa samples, in ten adenomas, 71 carcinomas and in ten liver metastases derived thereof, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 27 publications
2
32
1
Order By: Relevance
“…We have here observed a high expression level of complement resistance factors CD46, CD55 and CD59 on almost all cell lines. IHC studies of tumour samples from various stages of colorectal cancer, however, showed that CD59 and CD55 expression is far less frequent than seen with our tumour cell lines (Koretz et al, 1993;Hosch et al, 2001). As CD59 can interact with CD2 on T cells, there may even be a selective pressure against CD59 expression on tumour cells to avoid interaction with T cells (Hahn et al, 1992;Koretz et al, 1993).…”
Section: Mt201 Efficacy Against Breast Cancer Cell Lines N Prang Et Almentioning
confidence: 60%
“…We have here observed a high expression level of complement resistance factors CD46, CD55 and CD59 on almost all cell lines. IHC studies of tumour samples from various stages of colorectal cancer, however, showed that CD59 and CD55 expression is far less frequent than seen with our tumour cell lines (Koretz et al, 1993;Hosch et al, 2001). As CD59 can interact with CD2 on T cells, there may even be a selective pressure against CD59 expression on tumour cells to avoid interaction with T cells (Hahn et al, 1992;Koretz et al, 1993).…”
Section: Mt201 Efficacy Against Breast Cancer Cell Lines N Prang Et Almentioning
confidence: 60%
“…29 CD59 prevents cytolysis by binding to C8 and C9 and by inhibition of the C9-polymerization process. 30 Expression of these membrane complement regulators has been described for many tumors as well as for tumor cell lines of different origin, e.g., colon carcinoma, 31,32 melanoma, 33 breast carcinoma, 25 ovarian carcinoma 34 and tumors of the hematopoietic system. 35,36 Cumulative evidence supports the notion that membrane complement regulatory proteins are expressed in higher quantities in malignant tissue than in normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Cumulative evidence supports the notion that membrane complement regulatory proteins are expressed in higher quantities in malignant tissue than in normal tissue. 32,37,38 CD59 is considered as the main membrane complement regulatory protein restricting complement-mediated lysis of tumor cells. 39 K562 cells express high levels of CD59Ͼ CD46ϾCD55 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The study also reported increased CD55 expression in colon cancer tissues compared with normal tissues, which is consistent with our observations, although their study also found that low expression or even a lack of CD59 expression was a characteristic feature in colon cancer. 17,18 However, Thorsteinsson and colleagues 14 found that CD46 and CD59 (but not CD55) were highly expressed in the epithelium of colorectal cancer tissues. In addition, mCRPs have been shown to be localized only at the membrane.…”
Section: Commentmentioning
confidence: 99%
“…These results were notable because they differed from findings in previous studies. For example, Koretz and colleagues 17,18 investigated the expression of mCRPs in normal and cancerous colon tissues and found homogeneous, strong staining for CD46 in both types of tissues. The study also reported increased CD55 expression in colon cancer tissues compared with normal tissues, which is consistent with our observations, although their study also found that low expression or even a lack of CD59 expression was a characteristic feature in colon cancer.…”
Section: Commentmentioning
confidence: 99%